Social policy, protest participation and violent crime in Latin America - Tenorio, B (2015)
This thesis consists of four self-contained articles which focus on different aspects of citizens' demand for and governments' supply of social policy in Latin American democracies. The underlying questions that link the four papers are a) do social and economic grievances affect citizens' propensity to protest? and, b) do democratic governments in the region use social policy as an instrument to mitigate social discontent and violent crime? In the first two papers, I use public opinion data in order to examine the determinants of citizens' participation in protest with a special focus on dissatisfaction with the quality of public services, demands for inequality-reduction policies and economic deprivation. The results show that among other factors, protest participation is motivated by citizens' discontent over the quality of basic social services, support for redistributive policies, and relative economic deprivation. The third and fourth papers analyze the "supply side" of social spending in the region focusing on collective protest and violent crime, respectively. The third article argues that under democracy, organized labor is in a better position relative to other groups in society to obtain social policy concessions as a consequence of their collective action efforts. The results show that whereas social security spending increases as a consequence of labor militancy, cutbacks in human capital spending are less likely as peaceful large-scale demonstrations increase. The fourth paper argues that political leaders use education spending as an instrument to mitigate violent crime. It also argues that the effect of violent crime on education spending is larger when leftist governments are in power. The empirical analysis provides support for these arguments.